Rico Sabah Sdn. Bhd - Abdullah, Mohd Firdaus; Shamsudin, Mohd Hashree; Munasir, Naim (2022)
Through this Business Plan Project every member in our group be able to demonstrate some entrepreneurial skills in preparing a business plan. We did our best to finish the report with the guideline and assistance from our lecturer sir Mohd.Adzwin Faris Niasin. We experience such an amazing process through this project, as we learn a lot how to come out with a good business plan and how important research and knowledge in order to build a business. Administration and Organization Planning help us to be accurate about the business goals and future direction as we are determining the mission and vision of company we plan to build. Moreover, it helps as to determine the resources to achieve company targets and meet the business objective. In the other hands, Marketing Planning help the plan be more efficient as it is outlining business strategy that the company will use to generate leads and reach the company target market. Furthermore, Operation Planning process help us to aware about how the actual business should be operate. an ineffective and inefficient business operation may badly impact the business. Hence the businesses should be able to unsure the business operation system run without any problem in order to increase or to maintain product and customer service quality. Also, Operation Planning could help an organization to achieve a consistency and stability of the product and service provide to the customer. Finally, throughout this project we also learned about how to determine a business effort to achieve its objective and strategy by Financial Planning. The Plan describe every each of the activities, equipment, materials and resources that needed in a business to meet the business objective and include the time frame involved.